A cerium-based metal–organic framework having inherent oxidase-like activity applicable for colorimetric sensing of biothiols and aerobic oxidation of thiols. Issue 39 (27th September 2017) - Dalapati, Rana; Sakthivel, Balasubramanian; Ghosalya, Manoj K.; Dhakshinamoorthy, Amarajothi; Biswas, Shyam
Abstract : A cerium-based MOF exhibits oxidase-like activity for colorimetric sensing of biothiols and aerobic oxidation of thiols. Abstract : A cerium-based metal–organic framework (MOF;1 ) with a UiO-66 (UiO: University of Oslo) framework topology was synthesized solvothermally by employing 3, 4-dimethylthieno[2, 3- b ]thiophene-2, 5-dicarboxylic acid as a ligand. The MOF was thoroughly characterized by X-ray photoelectron spectroscopy (XPS), X-ray powder diffraction, infrared spectroscopy, and thermogravimetric and N2 sorption analyses. The activated material (1′ ) retained its structural integrity in water, acetic acid and 1 M HCl solution. XPS investigation reveals the presence of both Ce(iii ) and Ce(iv ) ions in1 . Owing to the presence of mixed-valence cerium ions, 1′ was able to oxidize the chromogenic peroxidase substrate 3, 3′, 5, 5′-tetramethylbenzidine (TMB) or 2, 2′-azinobis(3-ethylbenzothizoline-6-sulfonic acid) (AzBTS) in the absence of an external oxidizing agent. Thus, it showed inherent oxidase-like catalytic properties. Inspired by the excellent oxidase-mimicking activity of1′, a protocol was developed for the rapid colorimetric sensing of biothiols in NaAc buffer (0.2 M, pH = 4). The sensing ability of1′ towards cysteine was also demonstrated in human blood plasma. Furthermore, the redox-active cerium ions enabled1′ to exhibit excellent heterogeneous catalytic performance in aerobic oxidation catalysis of thiol compounds. The material is reusable (both as a sensor and as a catalyst), low-cost and highly stable, which renders it a promising candidate for the monitoring of biothiols in immunoassays and medical diagnosis as well as for industrial oxidation catalysis.